2023
DOI: 10.1029/2023wr034948
|View full text |Cite
|
Sign up to set email alerts
|

Linking Water Age, Nitrate Export Regime, and Nitrate Isotope Biogeochemistry in a Tile‐Drained Agricultural Field

Zhongjie Yu,
Yinchao Hu,
Lowell E. Gentry
et al.

Abstract: Accurately quantifying and predicting the reactive transport of nitrate () in hydrologic systems continues to be a challenge, due to the complex hydrological and biogeochemical interactions that underlie this transport. Recent advances related to time‐variant water age have led to a new method that probes water mixing and selection behaviors using StorAge Selection (SAS) functions. In this study, SAS functions were applied to investigate storage, water selection behaviors, and export regimes in a tile‐drained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 101 publications
2
2
0
Order By: Relevance
“…Overall, the accuracy of these values cannot be verified as the 'true' shape of the parameter's posterior density distribution is unknown. Nonetheless, values for the denitrification rate found in this study are within the ranges of other studies conducted in the same region (Nguyen et al, 2021;Yang, Heidbüchel, et al, 2018) and elsewhere Yu et al, 2023). The mass of denitrified N in the subsoil, along with its balance in the subsoil, is reported in Table S6, while for the N balance in the soil, we refer to the original studies of Nguyen et al (2021); .…”
Section: Denitrification Processessupporting
confidence: 83%
See 1 more Smart Citation
“…Overall, the accuracy of these values cannot be verified as the 'true' shape of the parameter's posterior density distribution is unknown. Nonetheless, values for the denitrification rate found in this study are within the ranges of other studies conducted in the same region (Nguyen et al, 2021;Yang, Heidbüchel, et al, 2018) and elsewhere Yu et al, 2023). The mass of denitrified N in the subsoil, along with its balance in the subsoil, is reported in Table S6, while for the N balance in the soil, we refer to the original studies of Nguyen et al (2021); .…”
Section: Denitrification Processessupporting
confidence: 83%
“…However, these results may be site-specific and not readily apply to all catchments. For example, in a recent study by Yu et al (2023) conducted in a tile-drained agricultural field, SAS functions were calibrated using chlorides, revealing a significant preference for young water more pronounced during wetter conditions, as observed in our study. Instead, the NO 3 À export regime was classified as chemostatic (i.e., NO 3 À concentrations remain stable over time) based on C-Q relationships, which was attributed to a substantial mixing volume and the absence of a pronounced vertical contrast in NO 3 À levels.…”
Section: Towards Improved Representation Of Nitrate Transport Modellingsupporting
confidence: 75%
“…Van Meter et al (2017) showed that nitrogen older than 50 years accounts for approximately 33% and 5% of the nitrogen at the basin outlet for the Mississippi (3 000 000 km 2 ) and Susquehanna (70 000 km 2 ) rivers. Smaller rivers have faster biogeochemical cycling of nitrate (Basu et al, 2011) travel time was expected, we would expect to see coupled enrichment of nitrogen and oxygen isotopes due to subsurface denitrification (Yu et al, 2023), that is, N and O isotopes will be enriched following a 1:1 to 1:0.5 line, but that is not the case here (Figure 7). Nitrate loading is driven primarily by patterns of surfacegroundwater interaction, as loading corresponds to when the stream is a losing and gaining stream within the cemetery reach and is shown in Figure 8, where we predominantly see the stream is losing both discharge and nitrate load or gaining both discharge and nitrate load on a given day.…”
Section: Nitrate In Meadowbrook Watershed With a Focus On St Mary's C...mentioning
confidence: 81%
“…The relevance of water transit times in relation to nitrate transport is pointed out in the study of van der Velde et al (2010) who investigated solute export at the Hupsel brook catchment and discovered the relationship between the dynamics of contact times of water and soil and the observed solute concentrations in stream. Nitrate transport in relation to water age was discussed by other studies (van der Velde et al, 2012;Molénat & Gascuel-Odoux, 2002;Kaandorp et al, 2021;Nguyen et al, 2021;Yu et al, 2023). Nitrate removal in relation to water age was explicitly pointed out by Benettin, Fovet, & Li (2020) who estimated water age based on chloride as tracer to analyze the relationship between water age and nitrate removal.…”
mentioning
confidence: 99%